2016
DOI: 10.3390/rs8070566
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Burn Severity Field Data and Very High Resolution GeoEye Images: The Case of the 2011 Evros Wildfire in Greece

Abstract: Abstract:Monitoring post-fire vegetation response using remotely-sensed images is a top priority for post-fire management. This study investigated the potential of very-high-resolution (VHR) GeoEye images on detecting the field-measured burn severity of a forest fire that occurred in Evros (Greece) during summer 2011. To do so, we analysed the role of topographic conditions and burn severity, as measured in the field immediately after the fire (2011) and one year after (2012) using the Composite Burn Index (CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…Topographical factors, that were not significant in this study, have clear influence on fire behaviour although the association between topography and burn severity cannot be generalized for all ecosystems and regions (Dragozi et al, 2016;Gonzalez-Olabarria et al, 2006;González et al, 2007) due to the prevalence of determined local conditions on the studied regions (for instance, variation on humidity between different elevations and aspects), or how the slope influences fire behaviour (higher slopes increase the rate of spread and intensity, but usually reduce the residence time of fire). Burn severity is expected to be more severe in coniferous forests than in broadleaved forests but in our study it did not appear as significant variable.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Topographical factors, that were not significant in this study, have clear influence on fire behaviour although the association between topography and burn severity cannot be generalized for all ecosystems and regions (Dragozi et al, 2016;Gonzalez-Olabarria et al, 2006;González et al, 2007) due to the prevalence of determined local conditions on the studied regions (for instance, variation on humidity between different elevations and aspects), or how the slope influences fire behaviour (higher slopes increase the rate of spread and intensity, but usually reduce the residence time of fire). Burn severity is expected to be more severe in coniferous forests than in broadleaved forests but in our study it did not appear as significant variable.…”
Section: Discussioncontrasting
confidence: 57%
“…Burn severity is expected to be more severe in coniferous forests than in broadleaved forests but in our study it did not appear as significant variable. The pre-fire tree species composition could play an important role in determining post-fire reflectance and recovery and, subsequently, burn severity (Dragozi et al, 2016). It is clear that, depending on the fire intensity and the specific response of the tree species to fire, different ecosystem responses such as resprouting and regeneration can be expected or be accentuated as time goes on (Keeley et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Biodiversity and related ecosystem services issues resulted as connected, also, to studies about environmental disturbance phenomena, like fire. Many papers in rs+pheno studies analyzed the role of wildfires' behavior both as a driver of vegetation recovery patterns [101][102][103] and as influenced by fuel phenology and flammability [104,105]. In this latter case, a high potential exists for characterizing, classifying, and mapping fuel based on rs+pheno dynamics.…”
Section: Emerging Research Topicsmentioning
confidence: 99%
“…Escuin et al [19] analyzed the capacity of NBR and NDVI indices derived from Landsat TM/ETM images for fire severity assessment in three fires that occurred in southern Spain. Dragozi et al [20] investigated the potential of GeoEye images on detecting the field-measured burn severity of a forest fire in Evros (Greece) during 2011. Results showed that remotely-sensed NDVI-based variables are able to encapsulate burn severity variability over time.…”
Section: Introductionmentioning
confidence: 99%